Analysis of protein, fat, and iron in catfish and green spinach biscuits - Mahalia, Lamia Diang; Harlyanti Muthma’innah Mashar; Sukmawati A. Damiti (Universitas Islam Indonesia, 2025)
Background: Stunting in Indonesia remains a significant health issue that cannot be overlooked. Stunting can be addressed through the consumption of foods derived from both animal and plant sources, which are high in protein and rich in essential amino acids beneficial for preventing stunting. The provision of biscuits fortified with catfish and spinach flour is anticipated to assist the government in reducing the prevalence of stunting.Objective: The aim of this study was to develop a functional food product formula utilizing catfish and spinach flour while also analyzing the nutritional content of the resultant biscuits.Method: This research employed three biscuit formulas with varying ratios of catfish and spinach flour, specifically F1 (15 g : 45 g), F2 (30 g : 30 g), and F3 (45 g : 15 g). Chemical analyses conducted on the biscuits included tests for moisture content and ash content using the gravimetric method, protein analysis utilizing the Kjeldahl method, fat analysis via the Soxhlet extraction method, and carbohydrate analysis employing the titrimetric method.Results: Based on the tests of the three biscuit formulas, it was found that the biscuits with formula F3 meet the minimum requirements outlined by the SNI, except for ash content. The protein content was 11.03%, the fat content was 31.073%, the water content was 2.26%, and the ash content was 2.98%. The protein content in formula F3 was higher than that in formulas F1 and F2 and has a high enough iron content at 5.025 mg/100 g.Conclusion: It can be concluded that biscuits with the F3 formula meet the nutritional values required by SNI regarding protein, fat, and water content. This formula has an opportunity for further development to enhance the carbohydrate, iron, and ash content of the biscuit to comply with SNI standards.